KONTEKSTUALISASI KONSEP JODOH, SAKINAH, MAWADAH, WARAHMAH DALAM AL-QUR’AN - Fawait Syaiful Rahman (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
Abstract Islam limits the pattern of interaction between men and women outside of marriage so that their respective honor can be maintained. In humans, there is a tendency of animal tendencies that have the potential to lead to prohibited cases (mungkarat or muharramat). Islam also regulates the provisions if a man and woman want a halal relationship as well as a reward value in the framework of marriage. An ideal marriage is generally defined as a marriage that is the result of one's own choice without any outside intervention, the two partners are never heard of fighting and arguing, and a married couple is supported by an established economy, such family conditions are considered ideal families. After several weeks or more, the news was heard that the husband and wife were divorced, even though at the beginning of the marriage they had received a prayer "hopefully they will become a sakinah family, mawadah, wa-rahmah and mate in the hereafter" could not prevent the intention to separate. The research method in this article uses a qualitative literature approach. The conclusion from the study and analysis of the text of the verses of the Qur'an regarding the concept of mate and the concepts of sakinah, mawadah, warahmah in the Koran is mentioned differently by Allah SWT. The concept of mate is said to use Arabic khalaqah, and the concepts of sakinah, mawadah, warahmah are spoken in Arabic ja'ala. The consequence of disclosing the concept of a mate using lafadz khlaqah means that something is the personal right of Allah SWT and humans do not have the effort to intervene, while the disclosure of the concepts of sakinah, mawadah, warahmah uses lafadz ja'ala, this means that human intervention is needed in building a family that is ideal.